The Influence of Attitudes on Environmental Activism Content on Social Media on the Desire to Support Environmental Issue Content - Asma Latifah; Benazir Bona Pratamawaty (Metacommunication: Journal of Communication Studies, 2024)
Now that we have entered an era of technological progress, a lot of social activism has started to take place on social media. There has been a lot of research discussing environmental activism that takes place on various social media. This research focuses on a person's attitude towards the circulation of environmental issues on social media. Attitude variables are taken from the TPB. Previous research examined all components of the TPB. However, this research only discusses attitudes that will have an influence. Apart from that, this research also discusses how a person's attitude after being exposed to environmental issue content can influence the desire to like the upload, donate, and volunteer. Research data was obtained using a precise quantitative method, namely by taking free samples. This method is carried out by distributing questionnaires on social media to make it easier for researchers to obtain samples that meet the criteria. Then the data obtained from distributing the questionnaires was analyzed using the SmartPLS and SPSS applications. From the results obtained, there is a positive relationship and significant influence between the predictor variables and the independent variables. This means that there really is an interplay between attitudes towards the content of environmental activism and the specified desires. Environmental activism content on social media is received positively by every individual. This is what makes them increasingly want to like environmental issue content, donate money and volunteer.